Coloniality, Legitimacy in Statebuilding, and the Use of Force in Africa - Samuel Ajogwu Igba and Emmaculate Asige Liaga (University of Johannesburg, 2021)
In Africa, legitimation and claims to the legitimate use of force are often challenged by the problematic nature of ethnic diversity, amongst other things. Although ethnicity and diversity are not the problems in themselves, the politicisation of ethnicity is. In this paper, we link this to a history of colonisation which clustered multiple ethnic groups together within single sovereign entities around the continent, as well as the current realities of coloniality which has prevented states within the continent from imagining and transcending the European artefact and design of the modern state in Africa. We link the exploratory term coloniality in statebuilding to the failure of African states to overcome the politicisation of ethnicity and ethnic diversity in order to mitigate the problematic nature of democracy in modern African states. This failure leads to challenges of legitimacy in any given state, and ultimately the states’ claim to the legitimate use of force. The resultant symptoms and indicators of such challenges are manifest in the rise of various insurgencies, separatism, and other forms of insecurity. The cases of Kenya, South Sudan, Nigeria, and Somalia are briefly discussed in this article, highlighting the problematic nature of the claims to the legitimate use of force, legitimacy, and the resultant political ethnicity with all its consequences for these states.